The Family Corner for the Post-COVID 19 Revitalization of Family Function - Sudirman, Sudirman; Ramadhita, Ramadhita; Bachri, Syabbul; Zuhriah, Erfaniah; Mahmudi, Zaenul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The COVID-19 pandemic has reduced family functions. During the COVID-19 pandemic, Indonesian families face three significant problems: distanced-family relations; neglected family education; and unequal socio-economic situation. This paper aims at explaining these three fundamental changes in family institutions. Besides, this paper identifies the factors that lead to family dysfunction. This article also offers concrete solutions to restore the lose of families function due to the COVID-19, i.e. the formation of a Family Corner. This research is a normative study using a critical, descriptive analysis method by presenting data from various literature and document sources. The latest data supported by several recent studies are described in detail in this paper. This research shows that post-pandemic family functions’ revitalization can be started by preparing a strong husband and wife’s emotional maturity.In addition, it is necessary to assist in communication and financial management of the family. Furthermore, revitalization will be successful if job opportunities are opened as widely as possible with incentive funds from the government and philanthropic institutions. Finally, the resolution and anticipation of natural disasters can be anticipated and resolved as quickly as possible. One of the effective ways for family revitalization is by establishing a Family Corner at each smallest unit of the society (Rukun Tetangga and Rukun Warga). Further research on this issue can be conducted through interviews with some informants who have experienced changes family lifestyle during the COVID-19 pandemic and mapping their hopes post pandemic period.